Alcohol production from potato cultivars in special and refuge selections (Research, Society and Development, 2020)
One third of all food produced is wasted in the world in the form of refuse, in 2018 alone more than 129 million tons of potatoes were wasted. One way to avoid such waste is to reuse them in ethanol generation. The objective of this work was to produce ethanol from the cultivars Divina Ágata and Orchestra in the special and refuse selections. For this, an exploratory, quali-quanti experimental study was carried out, where the potato was processed in the form of flour, a 2x2 factorial design with variation in yeast concentration and fermentation time, enzymatic hydrolysis with α-amylase and amyloglucosidase enzymes and fermentation at the ideal temperature conditions for each yeast. The must was distilled, the presence of alcohol, the alcohol content and the qualitative identification of the alcohol detected. The alcohol found was the ethanol with the highest alcohol content in the samples fermented by yeast S. pastorianus, at a concentration of 6 g L-1 and time of 3 days of fermentation with yield of 5.69% alcohol (v/v). From the obtained result, it is suggested that the use of refuse potatoes may be a viable alternative for the production of ethanol and, using S. pastorianus yeast, the alcoholic yield is more profitable, which reduces the waste of unmarketed potatoes.